The Concept of Ecodomy as Pedagogical Instrument in Intercultural Education - Simuț, Corneliu Cristian; Justus Liebig University Giessen (My University, 2024)
This cumulative doctoral project is an attempt to see how the concept of ecodomy can be used in intercultural education based on three already published articles (two published by myself as single author, and one that I co-authored with J. Buitendag) which deal with education as ecodomy, in conjunction with other nine articles that demonstrate how the concept of ecodomy can be applied in various domains of interest to tertiary education, especially to public universities, in intercultural contexts, such as Western settings and their African counterparts. Particularly, the concept of ecodomy will be treated as a pedagogical instrument in both these contexts, since it is related to the activity of teaching theology and religion as humanistic sciences, although I argue that the concept itself, as well as its content, should not be restricted to humanistic sciences alone. The purpose of using the concept of ecodomy as pedagogical instrument in intercultural education is to see if it can fit within the field of intercultural education and specifically in intercultural pedagogy. While the three articles on ecodomy are the core of this doctoral work and disclose no less than ten features of education as (a) science from the perspective of humanistic methodologies, the other nine articles reflect a palette of practical possibilities in which the concept of ecodomy could function as an educational instrument with factual relevance for various social contexts, beyond the boundaries of universities, in both Western and African situations.
Keywords: education; ecodomy; religion; intercultural; constructive; philosophy; ddc:370; ddc:100; ddc:200; ddc:230